2002
DOI: 10.1078/0944-5013-00162
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies on reference strains of mutans streptococci

Abstract: Twenty four reference strains (serotype a-h) belonging to the mutans group of streptococci were compared for DNA fragment patterns of rDNA after treatment with Hind III. It was shown that Streptococcus cricetus (serotype a), S. rattus (serotype b), and S. downei (serotype h) reveals comparatively homogeneous patterns while S. mutans (serotype c, e and f) exhibits differences between the different serotypes as well as within single serotypes. S. sobrinus had an intermediary diversity. These data support the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…pyogenes mentioned above, preparation of more mAbs is awaited to understand the immunobiology of oral streptococci responsible for dental caries and other streptococci responsible for tonsillitis, nephritis and other conditions in humans and animals. The number of serotypic variations by the mAbs are shown in table 4 and agrees well with that based on ribotype variations reported before [Ota et al, 2002].…”
Section: Serological Diversity Of Eight Serotypes Of Mutans Streptococcisupporting
confidence: 78%
See 2 more Smart Citations
“…pyogenes mentioned above, preparation of more mAbs is awaited to understand the immunobiology of oral streptococci responsible for dental caries and other streptococci responsible for tonsillitis, nephritis and other conditions in humans and animals. The number of serotypic variations by the mAbs are shown in table 4 and agrees well with that based on ribotype variations reported before [Ota et al, 2002].…”
Section: Serological Diversity Of Eight Serotypes Of Mutans Streptococcisupporting
confidence: 78%
“…After drying in the air, the membrane was exposed to UV light to fi x the DNA. Hybridisation was carried out as described previously [Ota et al, 2002] except that digoxigenin-labelled whole genomic DNA of reference strains was used as a probe.…”
Section: Eia For Antibody Specifi City and Serological Identifi Catiomentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these transmission patterns were detected despite the limited number of available isolates per subject, and may thus reflect an underestimation of the true level of homology among ms strains from family members. A recent study (25) suggested that S. mutans is genetically more diverse than S. sobrinus, a finding that may partly explain the higher homology of intrafamilial strains of S. sobrinus as well as the occurrence of an identical S. sobrinus ribotype in two unrelated subjects. This observation is in agreement with other studies (8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Newer systems are being developed such as terminal restriction fragment-length polymorphism (T-RFLP) [11,12], digoxigenin-labelled peptide nucleic acid to detect lactobacilli PCR amplicons immobilized on membranes from denaturing gradient gel electrophoresis [13] and enterobacterial repetitive intergenic consensus PCR (ERIC-PCR) and repetitive extragenic palindromic PCR (REP-PCR) [14]. This is important in order to differentiate reliable and proven strains and products from those of dubious quality as referenced above.…”
Section: Step One: Identify the Exact Strain That Is Being Usedmentioning
confidence: 99%